2016
DOI: 10.1002/hyp.10966
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of changing climate on the hydrology and hydropower production of the Tagus River basin

Abstract: The Tagus River basin is an ultimately important water source for hydropower production, urban and agricultural water supply in Spain and Portugal. Growing electricity and water supply demands, over‐regulation of the river and construction of new dams, as well as large inter‐basin and intra‐basin water transfers aggravated by strong natural variability of climate in the catchment, have already imposed significant pressures on the river. The substantial reduction of discharge is observed already now, and projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…The hydrological modelling carried out with the AR5 CC scenarios predicts a sharp decrease in the water resources of the THRB. These results are in line with the previous simulations made on the same scale (Lobanova et al, 2018), as well as on a larger scale (Guerreiro et al, 2017;CEDEX, 2011b;Lobanova et al, 2018). The hydrological modelling indicated that the increase in temperature would generate a decline in snowfall, which would lead to a reduction in the snow cover period of 2 months.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The hydrological modelling carried out with the AR5 CC scenarios predicts a sharp decrease in the water resources of the THRB. These results are in line with the previous simulations made on the same scale (Lobanova et al, 2018), as well as on a larger scale (Guerreiro et al, 2017;CEDEX, 2011b;Lobanova et al, 2018). The hydrological modelling indicated that the increase in temperature would generate a decline in snowfall, which would lead to a reduction in the snow cover period of 2 months.…”
Section: Discussionsupporting
confidence: 91%
“…These alterations of the hydrological processes will probably generate a change in the fluvial regime. In relative terms, the months of autumn (October, November, December) would suffer the major decrease, this change being consistent with the results of Lobanova et al (2018). At the annual level, these alterations would result in greater variability of the surface flows of the basin due to increases in the relative difference between the maximum and minimum flows of spring and summer, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This shows, a more frequent use of the models in Cluster A.1 in complex studies focusing on hydrological researches in large areas. On the other hand, the percentage of applications with the spatial category Regional is much lower in Cluster A.1 in comparison with Cluster A.2 (6.8% versus 43.7%; e.g., SWIM in Lobanova et al 2016). Also, the proportion of spatial category Catchment in Cluster A.1 is lower than in Cluster A.2 (4.5% versus 12.1%).…”
Section: Cluster Analysismentioning
confidence: 82%
“…Table 5 summarises the data on the evolution of water demands in the Tagus and Segura basins, as well as the available resources (taking into account the contemplated reduction from the HPI and District Plans) using what is known as the short series , the statistical trend that projects a greater reduction of supplies. It should be pointed out that in the Tagus basin, the situation of surface resources is compromised with regard to the satisfaction of demands of the basin in years of drought, and will be more so in view of the reduction in precipitation forecast by the climate change model [25]. Two other aspects of rainwater behavior that would also be altered (seasonality and irregularity) also cause concern in terms of water planning.…”
mentioning
confidence: 99%